Rui López de Segura contra el Brocense* - Gómez Gómez, Juan María (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
My essay analyses the critique made by the 16th century humanist Rui López de Segura in his gramatical work Grammaticae Institutiones on some of El Brocense´s grammatical ideas such as noun gender or case morphology and so on. In a closer reading of the Brocense´s works, however, that were available to Rui Lopez it can be ascertained that most of his critique has no scientific ground and reveals to a certain degree some personal bias. Besides, some specific data extracted from these invectives lead us into thinking that the Grammaticae Institutiones text that we are currently working with was published later than 1563, date shown on the front cover.My essay analyses the critique made by the 16th century humanist Rui López de Segura in his gramatical work Grammaticae Institutiones on some of El Brocense´s grammatical ideas such as noun gender or case morphology and so on. In a closer reading of the Brocense´s works, however, that were available to Rui Lopez it can be ascertained that most of his critique has no scientific ground and reveals to a certain degree some personal bias. Besides, some specific data extracted from these invectives lead us into thinking that the Grammaticae Institutiones text that we are currently working with was published later than 1563, date shown on the front cover.My essay analyses the critique made by the 16th century humanist Rui López de Segura in his gramatical work Grammaticae Institutiones on some of El Brocense´s grammatical ideas such as noun gender or case morphology and so on. In a closer reading of the Brocense´s works, however, that were available to Rui Lopez it can be ascertained that most of his critique has no scientific ground and reveals to a certain degree some personal bias. Besides, some specific data extracted from these invectives lead us into thinking that the Grammaticae Institutiones text that we are currently working with was published later than 1563, date shown on the front cover.My essay analyses the critique made by the 16th century humanist Rui López de Segura in his gramatical work Grammaticae Institutiones on some of El Brocense´s grammatical ideas such as noun gender or case morphology and so on. In a closer reading of the Brocense´s works, however, that were available to Rui Lopez it can be ascertained that most of his critique has no scientific ground and reveals to a certain degree some personal bias. Besides, some specific data extracted from these invectives lead us into thinking that the Grammaticae Institutiones text that we are currently working with was published later than 1563, date shown on the front cover.My essay analyses the critique made by the 16th century humanist Rui López de Segura in his gramatical work Grammaticae Institutiones on some of El Brocense´s grammatical ideas such as noun gender or case morphology and so on. In a closer reading of the Brocense´s works, however, that were available to Rui Lopez it can be ascertained that most of his critique has no scientific ground and reveals to a certain degree some personal bias. Besides, some specific data extracted from these invectives lead us into thinking that the Grammaticae Institutiones text that we are currently working with was published later than 1563, date shown on the front cover.